Analisis Penerapan Sistem Administrasi Umum Pada Divisi Administrasi PT Anugerah Santosa Abadi Di Surabaya - Nanda Oktavia; Jojok Dwiridotjahjono (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
The implementation of the General Administration System in the Administration Division of PT Anugerah Santosa Abadi (ASA) in Surabaya has a significant impact on the smooth operation of the company. This research highlights tax invoice and invoice management as a key element in daily administrative activities. Through a descriptive qualitative approach, this research aims to analyze the administrative practices implemented and their impact on company efficiency. The main objective of this research is to analyze the implementation of the general administration system, with a focus on the management of tax invoices and invoices, as well as identifying the impact on the smooth operations of PT ASA. This research uses a descriptive qualitative approach by carrying out an internship practice for one month at PT ASA. Data was collected through observation, interviews with administrative personnel, and analysis of documents related to tax invoices, invoices, and company tax policies. The research results show that PT ASA consistently applies two types of invoices, namely tax invoices and invoices, with clear roles and functions. Tax invoice color management contributes to the effectiveness of archiving and transaction tracking. Implementation of payment terms with the "Accurate" application also allows adaptation to the needs of customers from different sectors. Overall, good integration of administrative systems ensures company compliance with tax regulations and provides optimal service to customers. This research concludes that the implementation of the general administration system at PT ASA, especially in the management of tax invoices and invoices, makes a positive contribution to smooth operations and company compliance with tax regulations. The practical implication of this research is the importance of understanding and managing administrative aspects holistically to improve the efficiency and quality of company services.